The perfect storm: unraveling the interplay of genetic predisposition and viral triggers in type 1 diabetes pathogenesis - Veronese-Paniagua, Daniel A.; Millman, Jeffrey R. (Frontiers in Endocrinology, 2025)
Type 1 diabetes (T1D) is a chronic autoimmune disease characterized by the T cell-mediated destruction of insulin-secreting pancreatic β cells, leaving patients reliant on exogenous insulin to establish normoglycemia. Despite advancements in glucose management, the precise pathological mechanisms linking genetic predisposition and environmental triggers to the loss of immune tolerance remain incompletely understood, hindering the development of preventative therapies. This comprehensive review synthesizes clinical, experimental, and epidemiological data to detail the intricate pathogenesis of T1D, focusing on the convergence of autoimmunity, high-risk genetics, and enteroviral infection. We discuss how T1D is fundamentally a disease caused by failures in central and peripheral tolerance mechanisms, leading to the activation and infiltration of autoreactive CD4+ and CD8+ T cells into the pancreatic islets. We then explore the profound influence of genetic susceptibility, highlighting the role of HLA and non-HLA genes (e.g., IFIH1, TYK2) that modulate innate immune response, connecting genetic susceptibility to the pro-inflammatory response to pathogens. We also discuss enterovirus infection, particularly by coxsackievirus B (CVB), and its potential role as a critical environmental trigger. We demonstrate how CVB utilizes and subverts host cellular machinery to promote β cell stress and facilitate immune evasion, as well as evidence for its ability to establish a persistent low-grade infection within the pancreas. Finally, we emphasize the indispensable role of advanced human models, such as human pluripotent stem cell-derived islets. Elucidating the precise mechanisms linking genetic and viral risk factors in human-relevant contexts is critical. Future research must prioritize addressing these knowledge gaps to develop targeted, preemptive interventions that can successfully delay or prevent T1D onset.